Suppression of monosodium urate crystal-induced cytokine production by butyrate is mediated by the inhibition of class I histone deacetylases. Issue 3 (14th January 2015) - Cleophas, Maartje C P; Crişan, Tania O; Lemmers, Heidi; Toenhake-Dijkstra, Helga; Fossati, Gianluca; Jansen, Tim L; Dinarello, Charles A; Netea, Mihai G; Joosten, Leo A B
Abstract : Objectives: Acute gouty arthritis is caused by endogenously formed monosodium urate (MSU) crystals, which are potent activators of the NLRP3 inflammasome. However, to induce the release of active interleukin (IL)-1β, an additional stimulus is needed. Saturated long-chain free fatty acids (FFAs) can provide such a signal and stimulate transcription of pro-IL-1β. In contrast, the short-chain fatty acid butyrate possesses anti-inflammatory effects. One of the mechanisms involved is inhibition of histone deacetylases (HDACs). Here, we explored the effects of butyrate on MSU+FFA-induced cytokine production and its inhibition of specific HDACs. Methods: Freshly isolated peripheral blood mononuclear cells (PBMCs) from healthy donors were stimulated with MSU and palmitic acid (C16.0) in the presence or absence of butyrate or a synthetic HDAC inhibitor. Cytokine responses were measured with ELISA and quantitative PCR. HDAC activity was measured with fluorimetric assays. Results: Butyrate decreased C16.0+MSU-induced production of IL-1β, IL-6, IL-8 and IL-1β mRNA in PBMCs from healthy donors. Similar results were obtained in PBMCs isolated from patients with gout. Butyrate specifically inhibited class I HDACs. The HDAC inhibitor, panobinostat and the potent HDAC inhibitor, ITF-B, also decreased ex vivo C16.0+MSU-induced IL-1β production. Conclusions: In agreement with the reported low inhibitory potency of butyrate, a high concentration was needed for cytokine suppression, whereas synthetic HDAC inhibitors showed potent anti-inflammatory effects at nanomolar concentrations. These novel HDAC inhibitors could be effective in the treatment of acute gout. Moreover, the use of specific HDAC inhibitors could even improve the efficacy and reduce any potential adverse effects.